VARIASI EKSTRAK ETANOL BIJI ALPUKAT (Persea americana Mill.) PADA GRANUL EFFERVECSENT SEBAGAI ANTIDIABETES - Herwin Herwin; Hendra Herman (Fakultas Farmasi UMI, 2019)
This study aims to product the preparation effevecsent granule using variation of ethanol extract avocado seed (Persea americana Mill.) as antidiabetic using granulation method. This study was conducted using two formulas using variation of ethanol extract avocado seed (Persea americana Mill.) 1% and 10%, PVP K30 4%, Sodium cyclamate 0.1%, citric acid 0.2965 gram, tartric acid 0.5931 gram and sodium bicarbonate 1.0083 gram. The test results of evaluation preparation effevecsent granule using variation of ethanol extract avocado seed (Persea americana Mill.) showing that formulas 2 (two) is the best the result farmaceutic evaluation obtained with value Densitas Bulk = 2.82, Incompressible Density = 0.353, Carr’s Indeks = 17.12, Silent Angle = 19.790, Flow Time = 0.7, Time of Stopping Foam = 1.15. The test results of antidiabetic at in vivo formulas 2 (two) preparation effevecsent granule of ethanol extract avocado seed (Persea americana Mill.) using male mice (Mus musculus) with weight 176.5 mg, Initial Glucose Level = 87.5, Initial Glucose Induction = 249.5 obtained time of giving theraphy of formula at first day = 248.5, second day = 133, five day = 109 and seven day = 75.5, so preparation effevecsent granule of ethanol extract avocado seed (Persea americana Mill.) effective as antidiabetic.